PENGARUH HARGA DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK VIVO DI STORE PALEMBANG SQUARE - Amrillah Azrin (Fakultas Ekonomi Universitas Tridinanti Palembang, 2018)
Research to find out how much influence the price and brand in the decision of purchase of VIVO brand mobile phone at Mall Palembang Square. The calculation using spss regression coefficient is Y = 9.315 + 0.199X1 + 0.199X2 + e Constanta of 9.315 gives the sense that if the price variable and Brand equal zero (0) then the purchase decision of 9.315. If the price variable rises 1 unit then the purchase decision will rise by 0.199 assuming another variable is constant. And if the Brand Variable rises 1 unit then the purchase decision will rise by 0.199. Because the regression coefficient is positive, this can be interpreted if the price and brand variables are better, the purchase decision will go up. Keywords: Price, brand, purchase decision